Evaluation of monocot and eudicot divergence using the sugarcane transcriptome(1[w]) - Vincentz, M.; Cara, FAA; Okura, V. K.; da Silva, F. R.; Pedrosa, G. L.; Hemerly, A. S.; Capella, A. N.; Marins, M.; Ferreira, P. C.; Franca, S. C.; Grivet, L.; Vettore, A. L.; et al. (Amer Soc Plant Biologists, 2004)
Over 40,000 sugarcane (Saccharum officinarum) consensus sequences assembled from 237,954 expressed sequence tags were compared with the protein and DNA sequences from other angiosperms, including the genomes of Arabidopsis and rice (Oryza sativa). Approximately two-thirds of the sugarcane transcriptome have similar sequences in Arabidopsis. These sequences may represent a core set of proteins or protein domains that are conserved among monocots and eudicots and probably encode for essential angiosperm. functions. The remaining sequences represent putative monocot-specific genetic material, one-half of which were found only in sugarcane. These monocot-specific cDNAs represent either novelties or, in many cases, fast-evolving sequences that diverged substantially from their eudicot homologs. The wide comparative genome analysis presented here provides information on the evolutionary changes that underlie the divergence of monocots and eudicots. Our comparative analysis also led to the identification of several not yet annotated putative genes and possible gene loss events in Arabidopsis.